Analisis Potensi Pariwisata Di Kawasan Aerotropolis Yogyakarta International Airport (YIA) - M Alfian Nawari; Kartika Fajar Nieamah (Universitas Sains dan Teknologi Komputer, 2023)
Aerotropolis Yogyakarta International Airport has huge potential for tourism development, which includes three themes in the region's development, ecotourism, cultural tourism, and adventure tourism, and then developed by reference to the three main pillars of attraction - amenites-accessibility. As for the study, it aims to know about tourism in the Yogyakarta International Airport (yia) region of aerotropolis Yogyakarta International Airport (YIA) and the effect people have of developing tourism in the Yogyakarta International Airport (YIA) region. The study uses qualitative research methods. By using data collection techniques of observation, interview and documentation. Interviews use semi-structured techniques and data analysis using three techniques which are data reduction, data presentation and deduction drawing. Research shows that the Yogyakarta International Airport (YIA) region of aerotropolis Yogyakarta International Airport (YIA) has huge potential for an exciting tourism destination and contributes to economic growth and regional development. The positive effects of developing attractions in the aerotropolis include jobs, bringing revenue to the population, encouraging both tools and infrastructure improvements. Adverse effects on the environment, such as increased air pollution, water, or garbage.